1993
DOI: 10.1037/0022-3514.64.4.646
|View full text |Cite
|
Sign up to set email alerts
|

Integrating bottom-up and top-down theories of subjective well-being: The case of health.

Abstract: Part of the series International Handbooks of Quality-of-Life pp 239-268 The first presents a theoretical view of subjective wellbeing (SWB), which sets. Amazon.com: Handbook on Well-Being of Working Women (International Her research areas include quality of work life, subjective well-being, gender.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
229
1
12

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 342 publications
(264 citation statements)
references
References 33 publications
22
229
1
12
Order By: Relevance
“…As expected, the contextual factors were not the best predictors of SWB. The results support the top down theoretical models of SWB (Brief et al, 1993). However, the results also showed that the contextual variables significantly predicted SWB, particularly its cognitive dimension.…”
Section: The Main Predictors Of Swbsupporting
confidence: 75%
See 2 more Smart Citations
“…As expected, the contextual factors were not the best predictors of SWB. The results support the top down theoretical models of SWB (Brief et al, 1993). However, the results also showed that the contextual variables significantly predicted SWB, particularly its cognitive dimension.…”
Section: The Main Predictors Of Swbsupporting
confidence: 75%
“…material conditions; life events; sociopolitical contexts) on the subjective experience of individuals. According to this perspective, adverse circumstances affect SWB (Brief, Butcher, George, & Link, 1993;Feist, Bodner, Jacobs, Miles, & Tan, 1995). However, one of the main findings of this phase was that contextual factors are not the most powerful in explaining the variability of SWB.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Top-down theories of SWB such as the dynamic equilibrium model (Headey & Wearing, 1989) suggest that personality is a critical factor, potentially as a tendency to experience situations in a positive or negative way (Diener, 1984), or to return SWB to an equilibrium after life events have disturbed the balance (DeNeve & Cooper, 1998). These top-down approaches to SWB suggest that personality may influence the relationships between circumstances and outcomes, as well as having direct effects themselves (Brief, Butcher, George, & Link, 1993). In the case of organisational well-being, interaction theories could be interpreted to suggest that as well as having a direct effect, personality factors may influence the extent to which demands, effort, control, or reward have their effects on well-being.…”
Section: Predicting Well-being-personalitymentioning
confidence: 99%
“…Health perceptions refer to subjective evaluations of how people are feeling, and it is an important aspect of life satisfaction because life satisfaction may have a stronger correlation with health perception than with objective measures of health (Brief, Butcher, George, & Link, 1993). Research studies demonstrate that poor perceptions of health are significantly associated with diminished perceptions of life satisfaction for older adults (Jones, Rapport, Hanks, Lichtenberg, & Telmet, 2003;Leung, Moneta, & McBrideChang, 2005).…”
mentioning
confidence: 99%